The effect of the relative dose intensity of chemoradiotherapy on the effectiveness of therapy of locally advanced unresectable non-small cell lung cancer - A. E. Glukhareva; G. V. Afonin; I. V. Kolobaev; L. Yu. Grivtsova; S. A. Ivanov; A. D. Kaprin (Исследования и практика в медицине)
The purpose of the study. To estimate the number of patients with the preservation of relative dose intensity (RDI) ≥ 80 % of first-line antitumor therapy in patients with unresectable non-small cell lung cancer (NSCLC), and to compare the effectiveness of therapy in groups with optimal and lower RDI.Patients and methods. The study included 30 patients (25 men and 5 women) with locally advanced unresectable NSCLC. The median age was 57 years. The main criterion for inclusion in the study was morphologically verified NSCLC with stage IIIB-IIIC of the disease. All patients underwent simultaneous chemoradiotherapy. According to the histogenesis of the tumor process, patients with a squamous cell variant prevailed.Results. The data obtained from 22 (73.3 %) patients who retained a relative dose intensity of RDI > 80 % demonstrated that given dose intensity is sufficient to achieve a stable antitumor effect. In 8 (26.7 %) cases, however, the RDI was less than 80 %, which affected the effectiveness of the treatment. The median follow-up for overall survival (OS) was 29.2 months, progression-free survival (PFS) was 15.1 months, and local control was 21.9 months. in all patients included in the analysis. The indicators of OS in the second year had an advantage in the group of patients with RDI < 80 % and amounted to 73.3 % compared with 60.5 % in patients with RDI > 80 %. PFS was higher in the group of patients with high dose intensity, in the first year of follow-up it was 75.6 % compared with the group of patients with RDI < 80 % (62.5 %), in the second year of follow-up, PFS was 27.2 % and 20.8 %, respectively. Local control was 90.2 % in the first year in the group of patients with RDI > 80 % and 62.5 % in the group of patients with RDI < 80 %. The second year of follow-up demonstrated the advantage of the group of patients with RDI >80 % in terms of local control and amounted to 48.1 % versus 34.7 %, respectively.Conclusion. The results obtained show that maintaining relative dose intensity at a high level has a positive effect on survival rates and local control of patients with locally advanced unresectable NSCLC. However, there is a cohort of patients who did not receive the planned amount of treatment, due to the high toxicity of simultaneous chemoradiotherapy. It is necessary to develop new approaches to concomitant therapy aimed at reducing the toxicity of the combined treatment and achieving maximum antitumor effect.